Consensus guidelines on the testing and clinical management issues associated with HLA and non-HLA antibodies in transplantation - Tait, Brian D.; Süsal, Caner; Gebel, Howard M.; Nickerson, Peter W.; Zachary, Andrea A.; Claas, Frans H. J.; Reed, Elaine F.; Bray, Robert A.; Campbell, Patricia; Chapman, Jeremy R.; Coates, P. Toby; Colvin, Robert B.; et al. (Transplantation, 2013)
Background: The introduction of solid-phase immunoassay (SPI) technology for the detection and characterization of human leukocyte antigen (HLA) antibodies in transplantation while providing greater sensitivity than was obtainable by complement-dependent lymphocytotoxicity (CDC) assays has resulted in a new paradigm with respect to the interpretation of donor-specific antibodies (DSA). Although the SPI assay performed on the Luminex instrument (hereafter referred to as the Luminex assay), in particular, has permitted the detection of antibodies not detectable by CDC, the clinical significance of these antibodies is incompletely understood. Nevertheless, the detection of these antibodies has led to changes in the clinical management of sensitized patients. In addition, SPI testing raises technical issues that require resolution and careful consideration when interpreting antibody results. - Methods: With this background, The Transplantation Society convened a group of laboratory and clinical experts in the field of transplantation to prepare a consensus report and make recommendations on the use of this new technology based on both published evidence and expert opinion. Three working groups were formed to address (a) the technical issues with respect to the use of this technology, (b) the interpretation of pretransplantation antibody testing in the context of various clinical settings and organ transplant types (kidney, heart, lung, liver, pancreas, intestinal, and islet cells), and (c) the application of antibody testing in the posttransplantation setting. The three groups were established in November 2011 and convened for a “Consensus Conference on Antibodies in Transplantation” in Rome, Italy, in May 2012. The deliberations of the three groups meeting independently and then together are the bases for this report. - Results: A comprehensive list of recommendations was prepared by each group. A summary of the key recommendations follows. Technical Group: (a) SPI must be used for the detection of pretransplantation HLA antibodies in solid organ transplant recipients and, in particular, the use of the single-antigen bead assay to detect antibodies to HLA loci, such as Cw, DQA, DPA, and DPB, which are not readily detected by other methods. (b) The use of SPI for antibody detection should be supplemented with cell-based assays to examine the correlations between the two types of assays and to establish the likelihood of a positive crossmatch (XM). (c) There must be an awareness of the technical factors that can influence the results and their clinical interpretation when using the Luminex bead technology, such as variation in antigen density and the presence of denatured antigen on the beads. Pretransplantation Group: (a) Risk categories should be established based on the antibody and the XM results obtained. (b) DSA detected by CDC and a positive XM should be avoided due to their strong association with antibody-mediated rejection and graft loss. (c) A renal transplantation can be performed in the absence of a prospective XM if single-antigen bead screening for antibodies to all class I and II HLA loci is negative. This decision, however, needs to be taken in agreement with local clinical programs and the relevant regulatory bodies. (d) The presence of DSA HLA antibodies should be avoided in heart and lung transplantation and considered a risk factor for liver, intestinal, and islet cell transplantation. Posttransplantation Group: (a) High-risk patients (i.e., desensitized or DSA positive/XM negative) should be monitored by measurement of DSA and protocol biopsies in the first 3 months after transplantation. (b) Intermediate-risk patients (history of DSA but currently negative) should be monitored for DSA within the first month. If DSA is present, a biopsy should be performed. (c) Low-risk patients (nonsensitized first transplantation) should be screened for DSA at least once 3 to 12 months after transplantation. If DSA is detected, a biopsy should be performed. In all three categories, the recommendations for subsequent treatment are based on the biopsy results. - Conclusions: A comprehensive list of recommendations is provided covering the technical and pretransplantation and posttransplantation monitoring of HLA antibodies in solid organ transplantation. The recommendations are intended to provide state-of-the-art guidance in the use and clinical application of recently developed methods for HLA antibody detection when used in conjunction with traditional methods.
Gesehen am 27.01.2022